Method for detecting mixing uniformity of resin-based composite material and application thereof
Differential scanning calorimetry (DSC) was used to detect the local sites of resin-based composite materials, analyze the endothermic peak area, solve the problem of difficult detection of the mixing uniformity of resin-cured dosage-form composite materials, and achieve efficient and accurate quality control.
Patent Information
- Application Number
- CN202510674528.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-08-29
AI Technical Summary
The prior art is difficult to directly and accurately detect the mixing uniformity of resin-cured dosage form composite materials, resulting in inaccurate detection results and difficult to control product quality in actual production.
Differential scanning calorimetry (DSC) is used to sample and detect local sites of the product. By analyzing the endothermic peak area of the DSC curve, the endothermic average value is calculated, and the mixing uniformity is judged.
The direct and accurate detection of the mixing uniformity of resin-based composite materials is achieved, which can facilitate the control of product quality in industrial production, avoid waste and improve production efficiency.
Smart Images

Figure CN120559019A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite material detection, and in particular to a method for detecting mixing uniformity of a resin-based composite material and an application thereof. Background Art
[0002] To test whether a resin-curing agent composite material is uniformly mixed, the degree of cure is currently primarily measured indirectly. Current methods for testing degree of cure include the HB 7614 Differential Scanning Calorimetry (DSC) test method for determining the degree of cure of composite resin matrices and the GB / T 2576 test method for determining the insoluble content of fiber-reinforced plastic resins.
[0003] According to the relevant standards of HB 7614, it is necessary to test the homogeneous liquid, which means that the specific ratio of the two components of the basic sample needs to be set in advance (such as Figure 10 (as shown) and ensuring sufficient and uniform mixing. The degree of mixing uniformity is measured by setting different ratios. Product samples are then taken for curing tests, and the specific ratio of the two components in the product samples is determined by reverse engineering. However, this testing method presupposes that the base sample must be uniformly mixed. However, in actual production, the degree of mixing uniformity varies from sample to sample, and even from sample to sample. It is impossible to predict the two-component ratio at each test location in advance, making the HB 7614 test method less feasible in practical applications.
[0004] GB / T 2576, a traditional chemical dissolution method, requires different solvent combinations for different resins. This can lead to incomplete dissolution of some resin systems, potentially resulting in an overestimation of the insoluble content. Furthermore, GB / T 2576 also has limitations in terms of ease of use, measurement accuracy, and method applicability.
[0005] Existing technology can also indirectly characterize the degree of curing by conducting hardness tests on composite materials, and then characterize the degree of mixing uniformity through the degree of curing. However, the hardness of the product is related to multiple factors such as fiber layup, resin impregnation, porosity, etc., so there is no absolute relationship between uneven mixing of the two components and the hardness of the product.
[0006] In view of the above situation, a method is needed that can directly detect the mixing uniformity of the two components of a composite material and has more accurate detection results. Summary of the Invention
[0007] The purpose of the present invention is to provide a method for detecting the mixing uniformity of resin-based composite materials and its application, so as to solve the technical problem in the prior art that the homogeneity of the resin-curing agent composite material mixture is difficult to visually detect.
[0008] In order to solve the above technical problems, the present invention specifically provides the following technical solutions:
[0009] The present invention provides a method for detecting mixing uniformity of a resin-based composite material, comprising the following steps:
[0010] Using differential scanning calorimetry, local sites of the product are sampled and tested to obtain a DSC curve with heat flow rate dH / dt as the ordinate and temperature T as the abscissa;
[0011] Sampling and testing a plurality of local sites of the product to obtain a plurality of DSC curves, and dividing the sum of the endothermic peak areas of all the DSC curves by the number of the local sites to obtain an endothermic average value;
[0012] The magnitude of the average value of the endothermic value is negatively correlated with the homogeneity of the product mixing.
[0013] As a preferred embodiment of the present invention, the product is an epoxy resin composite material containing at least bisphenol A resin and an amine curing agent.
[0014] As a preferred embodiment of the present invention, the differential scanning calorimetry method comprises the following steps:
[0015] Adding the bisphenol A resin and the amine curing agent into a rubber mixing head to obtain the product;
[0016] Ensure that parameters such as flow rate and pressure remain unchanged and hedge and mix the products;
[0017] Pour the mixed liquid from the mixing head into the mold of the flat vulcanizer, ensure that the mold is at 80-85°C, keep it warm for 90 minutes, cool it for 30 minutes and then open the mold;
[0018] The product samples were taken for DSC testing.
[0019] The present invention provides an application of a method for detecting the mixing uniformity of a resin-based composite material in the detection of the homogeneity of an epoxy resin composite material. The higher the average endothermic value, the smaller the homogeneity of the epoxy resin composite material; the lower the average endothermic value, the greater the homogeneity of the epoxy resin composite material.
[0020] As a preferred embodiment of the present invention, the epoxy resin composite material is a bisphenol A-amine curing agent system.
[0021] The invention provides an application of a method for detecting the mixing uniformity of a resin-based composite material in a device for detecting the quality of a bisphenol A-amine curing agent system.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention can directly detect local sites of a cured product through differential scanning calorimetry, obtaining a DSC curve with heat flow rate dH / dt as the ordinate and temperature T as the abscissa. The endothermic peak in the DSC curve can be used to determine whether the local site of the sample is uniformly mixed. This method can directly determine whether the epoxy resin composite material of the bisphenol A-amine curing agent system is a homogeneous liquid, without the need to detect the degree of curing. The test results are not affected by other reaction conditions and are highly accurate.
[0024] The present invention processes the sum of the areas of the endothermic peaks in several local sites to obtain an endothermic average value. The size of the endothermic average value is negatively correlated with the homogeneity of the product mixing, so that the homogeneity of the overall reaction of the epoxy resin composite material can be quantified, and the direct detection of the homogeneity of the epoxy resin composite material can be achieved. In the field of industrial production, the judgment of the system homogeneity can facilitate the composite material in each link of production. After obtaining sufficient homogeneity, the next step of production can be carried out, thereby avoiding waste and improving the homogeneity of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the description of the prior art. Obviously, the drawings described below are merely exemplary, and those skilled in the art can derive other implementation drawings based on the provided drawings without inventive effort.
[0026] Figure 1 A schematic flow chart of a method for detecting mixing uniformity of a resin-based composite material is provided for the present invention;
[0027] Figure 2 Provide the endothermic peak statistics of Group 1 in Example 1 of the present invention;
[0028] Figure 3 Provide the endothermic peak statistics of group 2 in Example 1 of the present invention
[0029] Figure 4 The present invention provides a DSC test result diagram of the single-component bisphenol A epoxy resin in Example 2;
[0030] Figure 5 The present invention provides a DSC test result diagram of the glass fiber in Example 2;
[0031] Figure 6 The present invention provides a DSC test result diagram of the single-component amine curing agent in Example 2;
[0032] Figure 7Provides a physical picture of the product produced by the mixing of different mixing heads in Example 3 of the present invention;
[0033] Figure 8 The present invention provides a statistical chart of the Barcol hardness test of products produced by different mixing heads in Example 3;
[0034] Figure 9 Provides a statistical diagram of the endothermic peaks of the products produced by different mixing heads in Example 3 of the present invention
[0035] Figure 10 A comparative statistical chart of the degree of cure of basic samples set for the differential scanning calorimetry (DSC) test method in the prior art. DETAILED DESCRIPTION
[0036] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0037] like Figure 1 As shown, the present invention provides a method for detecting the mixing uniformity of a resin-based composite material, comprising the following steps: using a DSC instrument and adopting differential scanning calorimetry to detect a local site of the product, and obtaining a DSC curve with heat flow rate dH / dt as the ordinate and temperature T as the abscissa;
[0038] Sampling and testing are performed on several local sites of the product to obtain several DSC curves. The sum of the endothermic peak areas of all DSC curves is divided by the number of local sites to obtain the average endothermic value. The size of the average endothermic value is negatively correlated with the homogeneity of the product mixing.
[0039] Differential scanning calorimetry is mainly based on the use of a differential scanning calorimeter (DSC instrument), and its use is a well-known technique and will not be described in detail.
[0040] The present invention does not require sample preparation in advance. Its main method is to analyze the curing agent content in the existing product to analyze whether there is curing agent residue in each local site of the product. If there is curing agent residue, an endothermic peak will appear. The more curing agent residue, the larger the area of the endothermic peak. If the endothermic peak area of some local sites is particularly large, it means that the content of curing agent here is very high, that is, the product is very uneven. If no endothermic peak appears in several local sites, it means that the curing agent has reacted completely and the product is relatively uniform.
[0041] It can be seen that the detection method proposed in the present invention is related to the special properties of the curing agent, namely, its ability to exhibit an endothermic peak during differential scanning calorimetry detection, while materials such as resins and fibers do not exhibit endothermic peaks, and no endothermic peaks are present in the product of a complete reaction. Therefore, for resin composite materials, there is a unique corresponding relationship between the residual amount of the curing agent and whether it has an endothermic peak.
[0042] If one wishes to determine the amount of residual curing agent, one can first infer the relationship between its concentration and residual amount by measuring the endothermic peak area of the curing agent. The proportional relationship is specifically related to the type of curing agent.
[0043] This method for testing product homogeneity not only determines whether the product is evenly mixed, but also assesses its quality and whether its hardness meets the required standards. It can be inferred that if the average heat absorption value is high and the homogeneity is low, the hardness will often fall short of the required standards. If the average heat absorption value is low and the homogeneity is high, the hardness will be closer to the required standards. If the average heat absorption value approaches zero, the degree of solidification is high and the hardness is considered to meet the required standards.
[0044] Theoretically, the greater the number of local sites, the better the detection effect of sample homogeneity. In the detection method disclosed in the present invention, as long as the endothermic peak area of the DSC curve of one site is greater than, it indicates that the epoxy resin composite material at this local site is not mixed uniformly.
[0045] The above endothermic peak areas do not take negative numbers into account.
[0046] The following is explained through multiple embodiments:
[0047] Example 1 - The product obtained by the reaction of bisphenol A epoxy resin and amine curing agent detected an endothermic peak in the DSC instrument
[0048] Group 1 and Group 2 are selected. Group 1 and Group 2 have the same resin content; and the amount of curing agent is greater than the amount of resin;
[0049] The difference is that compared with group 1, the curing agent content in group 2 is higher.
[0050] Differential scanning calorimetry was used to sample and test local sites of the products of Group 1 and Group 2, and a DSC curve was obtained with the heat flow rate dH / dt as the ordinate and the temperature T as the abscissa.
[0051] See the results Figure 2 and Figure 3 As shown, Figure 2 and Figure 3 Both showed endothermic peaks and Figure 3 The endothermic peak area is larger than Figure 2This is inconsistent with the exothermic phenomenon of the cross-linking reaction. It can be seen that for excess curing agent, it can show endothermic phenomenon in DSC measurement.
[0052] Example 2 - Only the curing agent exhibits endothermic properties
[0053] DSC tests were conducted on one-component bisphenol A epoxy resin, one-component amine curing agent, and glass fiber. Figure 4 、 Figure 5 as well as Figure 6 As shown, in Figure 6 In the case of amine curing agents, an endothermic peak appears at about 40°C. Figure 2 、 Figure 3 The ranges are basically consistent, and there is no endothermic / exothermic peak in the resin and glass fiber.
[0054] It can be seen that for a composite material containing bisphenol A epoxy resin and an amine curing agent, if the amine curing agent cannot completely react with the single-component bisphenol A epoxy resin and a residue is left, it will absorb heat in the DSC test.
[0055] The following further provides examples to illustrate that the size of the endothermic peak is related to the degree of homogeneity of the system:
[0056] Example 3:
[0057] The experimental steps are as follows:
[0058] 1. Use five mixing heads (numbered 1-5) to prepare the product. Mixing heads 1-5 contain the same reactants, but the difference is that the mixing effect increases in sequence, and mixing head 5 has a more uniform mixing effect.
[0059] 2. Ensure that parameters such as flow rate and pressure remain unchanged and perform hedging and mixing;
[0060] 3. Pour the mixed liquid from different mixing heads into the mold of the flat vulcanizing machine;
[0061] 4. Ensure the mold is at 80-85℃, keep warm for 90 minutes, cool for 30 minutes before opening the mold;
[0062] 5. Analyze the degree of curing of the product surface;
[0063] 6. Conduct hardness test on the product;
[0064] 7. Take samples of the product for DSC testing.
[0065] from Figure 7 and Figure 8It can be seen that as the mixing uniformity becomes better, the average Barcol hardness of the product increases, the endothermic peak area generated by the decomposition of the curing agent becomes smaller and smaller, and the starting temperature of the endothermic peak gradually increases. Product No. 5 has no obvious endothermic peak / exothermic peak, which can be considered to be uniformly mixed, the cross-linking reaction is complete, and the degree of curing is high.
[0066] from Figure 9 It can be seen that curve No. 3 has an exothermic peak in the range of 40-60°C. It may be that the product has an error (slightly lower holding temperature or slightly shorter holding time), resulting in incomplete cross-linking reaction.
[0067] In this verification example, samples were taken from the center area of the product. It is worth noting that there are uncured areas in the center area of products 1-4, and as the mixing effect increases, the uncured area in the center area decreases, and the surface of product No. 5 is completely cured.
[0068] If you want to conduct a local mixing uniformity test on the product, you need to take samples at the required location for testing; if you want to check the overall mixing uniformity of the product, you should take samples at multiple locations and measure the average value of the endothermic peak area to more accurately judge the overall mixing uniformity of the product.
[0069] The following is an analysis of what will happen to the DSC curve:
[0070] 1. For a single DSC curve, the appearance of an endothermic peak indicates that there is residual curing agent at this local sampling site, and the larger the endothermic peak area, the more residual curing agent;
[0071] 2. For a single DSC curve, if an exothermic peak appears, it means that the cross-linking reaction at the local site is not complete, and the curing conditions can be further optimized;
[0072] 3. If there is no obvious endothermic / exothermic peak, it means that the cross-linking reaction at this local site is complete, and it is considered that the mixture is uniform and has been completely cured;
[0073] 4. For the DSC curves of different local sampling sites in multiple identical products, the average value of the endothermic absorption is used to judge the degree of mixing uniformity. The larger the average value, the more curing agent content that has decomposed without undergoing cross-linking reaction, which proves that the mixing is more uneven; the smaller the average value, the less curing agent content that has decomposed without undergoing cross-linking reaction, and the more uniform the system mixing.
[0074] The present invention simulates the heterogeneity of a two-component epoxy resin sample of a bisphenol A-amine curing agent system by using an excess curing agent. Since the amine curing agent will undergo a decomposition reaction during heating, the heterogeneity is obtained by DSC instrument detection and analysis.
[0075] It can be seen that for epoxy resin material systems with better curing degree, the less residual curing agent there is, and therefore the smaller the endothermic peak area detected by the DSC instrument will be. In the DSC curve with heat flow rate dH / dt as the vertical coordinate and temperature T as the horizontal coordinate, several local sites of the product are sampled and tested to obtain several DSC curves. The sum of the endothermic peak areas of all DSC curves is divided by the number of local sites to obtain the endothermic average value. The size of the endothermic average value is negatively correlated with the homogeneity of the product mixing.
[0076] In a single DSC curve, if the DSC curve contains an exothermic peak, the cross-linking reaction at the local site is in progress; if an endothermic peak appears in the DSC curve, the local site is unevenly mixed; if there is no endothermic peak or exothermic peak in the DSC curve, the local site is evenly mixed and completely cured.
[0077] This detection method can be used in the ratio optimization of substrate reactions. For example, under continuous stirring, during the reaction process of the reactants, several parts of the sample are extracted and tested at multiple time points. It is found that the endothermic peaks exist for a long time and the difference between the areas is not large. At this time, it is concluded that there is too much curing agent. This phenomenon can be avoided by reducing the use of curing agent. In actual industrial production, the optimal ratio of reactants can also be adjusted according to this method to prevent the occurrence of excessive amounts of a certain reactant, avoid waste, reduce production costs, and facilitate detection.
[0078] This detection method can be used to optimize reaction mixing time. For example, after the reactant ratio is confirmed, under continuous stirring, several parts of the sample are extracted and tested at multiple time points during the reaction process until the endothermic / exothermic peak disappears. At this time, the extracted sample is at the time when the reaction is complete. In actual industrial production, this method can be used to adjust the optimal mixing time of the reactants to prevent waste of insufficient or excessive stirring time. The verification method is simple.
[0079] This detection method can be used to optimize the reaction temperature and reaction conditions. For example, after the reactant ratio is confirmed and the reaction time is determined, if a local exothermic peak area of the sample is found, it may be that the reaction temperature and insulation conditions are not up to standard. In this case, it is necessary to optimize the above reaction conditions and increase the reaction temperature. In actual industrial production, this method can also be used to improve insulation measures, so that the cross-linking reaction of the composite material can be within production expectations, reducing the time cost of production and making the detection method convenient.
[0080] This detection method can be used to screen mixing methods and instrumentation. For example, after confirming the reactant ratio and reaction temperature, extract and test several local areas of the sample at multiple time points under continuous stirring. If the average value of the heat absorption area remains constant over a long period of time, the system is not homogeneous enough and the stirring rate or stirring method needs to be adjusted to achieve faster homogeneous mixing. In actual industrial production, this method can also be used to adjust the stirring rate and stirring mechanism of the reactants to improve the homogeneity of the reactants.
[0081] Based on the above application, this detection method can also be applied to a device for detecting the homogeneity of a two-component resin composite material containing bisphenol A resin and an amine curing agent.
[0082] The method and application of detecting the mixing uniformity of resin-based composite materials of this embodiment are suitable for verifying the homogeneity, optimal reactant ratio, reaction temperature, mixing conditions and reaction time of a two-component epoxy resin reaction in a bisphenol A-amine curing agent system.
[0083] The above embodiments are merely exemplary embodiments of the present application and are not intended to limit the scope of the present application. The scope of protection of the present application is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present application within the essence and scope of protection of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the scope of protection of the present application.
Claims
1. A method for detecting the mixing uniformity of a resin-based composite material, characterized in that: The steps include: Using differential scanning calorimetry, local sites of the product are sampled and tested to obtain a DSC curve with heat flow rate dH / dt as the ordinate and temperature T as the abscissa; Sampling and testing a plurality of local sites of the product to obtain a plurality of DSC curves, and dividing the sum of the endothermic peak areas of all the DSC curves by the number of the local sites to obtain an endothermic average value; The magnitude of the average value of the heat absorption is negatively correlated with the homogeneity of the product mixture; The product is an epoxy resin composite material containing at least bisphenol A resin and an amine curing agent.
2. The method for detecting mixing uniformity of a resin-based composite material according to claim 1, characterized in that: The differential scanning calorimetry method comprises the following steps: Adding the bisphenol A resin and the amine curing agent into a rubber mixing head to obtain the product; Ensure that parameters such as flow rate and pressure remain unchanged and hedge and mix the products; Pour the mixed liquid from the mixing head into the mold of the flat vulcanizer, ensure that the mold is at 80-85°C, keep it warm for 90 minutes, cool it for 30 minutes and then open the mold; The product samples were taken for DSC testing.
3. An application of the detection method according to claim 1 or 2 in the homogeneity detection of epoxy resin composite materials.
4. The use according to claim 3, wherein the epoxy resin composite material is a bisphenol A-amine curing agent system.
5. Use of the detection method according to any one of claims 1 to 4 in a device for detecting the quality of a bisphenol A-amine curing agent system.